Towards safer societies. Punishment, masculinities and violence against women - Snider, Laureen (The British journal of criminology, 1998)
This paper seeks to look beyond criminalization models to examine what is known about building less violent societies, at the macro, middle and micro levels. It argues that criminalization is a flawed strategy for dealing with male violence againist women caused by a failure to theorize social control adequately, a failure that has led feminists and other progressive social movements to mis-identify penality as synonymous wrth social control. The first part examines the realities of agendas of criminalization and increased punitiveness through incarceration rates. The second part seeks to explain the dependence on criminal law and institutions of criminal justice by feminists and new social movements. Focusing on wife assault and battery, it points out that strategies of criminalization have benefited privileged white women at the expense of women of colour, aboriginal and immigrant women, and points out problems with the failure to engender concepts of social control. The third part looks at what we know about policies, strategies and identities with the potential to transcend criminalization and facilitate social transformation, paying special attention to the construction, roots and maintenance of hegemonic masculinity. Overall it is argued that effective social control of aberrant behaviour must be sought outside criminal justice institutions, and that the feminist and progressive focus should shift towards examining how to create less violent people (particularly men), families, communities and societies